Hysteresis performance of section steel reinforced concrete-filled rectangular stainless steel tubular columns - Enpu Xie; Yang Wang; Yibei Bao; Kun Huang; Xianjiang Zhang (SN Applied Sciences, 2023)
Abstract Due to high bearing capacity and excellent seismic performance, the section steel reinforced concrete-filled rectangular steel tube has been widely applied in engineering. The application of stainless steel for outer steel tube can improve the durability performance of members. In this study, ABAQUS software was used to perform nonlinear seismic analysis on section steel reinforced concrete-filled rectangular stainless steel tubular columns, and the numerical model was validated against experimental data. The mechanism and parametric study of the hysteresis performance were conducted. These parameters mainly include: concrete strength, strength of stainless steel, strength of section steel, steel ratio of stainless steel tube, steel ratio of section steel, axial compression ratio, and slenderness ratio. The analysis results showed that: increasing the strength of stainless steel tube and concrete can significantly improve the bearing capacity of members, but the strength of section steel has little effect; the bearing capacity decreases with the increasing slenderness ratio; when the axial compression ratio is smaller than 0.4, increasing axial compression can improve the bearing capacity. The strength of each material shows little influence on the shape of load–displacement skeleton; the axial compression ratio presents high effect on the shape of descending stage of curve, and the larger the axial compression ratio, the steeper the descending stage; the slenderness shows high influence on curve shape, and the larger the slenderness, the less the elastic stiffness, and the more gentle the descending stage of curve. Finally, a simplified load–displacement hysteretic model was proposed, which exhibits good agreement with finite element numerical analysis.